2017
DOI: 10.3126/jnhrc.v15i2.18192
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Percutaneous Nephrolithotomy in Children

Abstract: Background: Renal stone disease is a common problem in children in developing countries. Its prevalence in children varies from 5% to 15%. It is suggested that anatomic abnormalities, recurrent urinary tract infections, metabolic disturbances, dietary and environmental factors are the predisposing factors.The aim of this study is to evaluate the safety and efficacy of percutaneous nephrolithotomy in children.Methods: Between May 2012 and Dec 2016, 25 children with renal stone diseases underwent percutaneous ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…Dongol et al reported a stone free rate of 88% in a study of 25 children with complication rate of 12%. 13 Higher rate of 30.3% has been reported by Mousavi-Bahar et al which included severe complications renal parenchymal and duct injury, colon perforation, damage to major vessels, pneumothorax and hemothorax. 14 Fever has been reported as common postoperative complication which was seen in 12.3% patients in our study.…”
Section: Resultsmentioning
confidence: 85%
“…Dongol et al reported a stone free rate of 88% in a study of 25 children with complication rate of 12%. 13 Higher rate of 30.3% has been reported by Mousavi-Bahar et al which included severe complications renal parenchymal and duct injury, colon perforation, damage to major vessels, pneumothorax and hemothorax. 14 Fever has been reported as common postoperative complication which was seen in 12.3% patients in our study.…”
Section: Resultsmentioning
confidence: 85%
“…Our length of hospital stay duration of nephrostomy tube in situ is comparable to previously published data. 42.85% of our cases were tubeless, which is safe when performing uncomplicated PCNL [26][27][28][29][30][31][32][33][34]. Prior renal surgery on the same side didn't have any impact on outcome of PCNL [35].…”
Section: Discussionmentioning
confidence: 99%
“…Согласно данным U.M.S. Dongol и соавт., основными осложнениями ЧНЛТ являются гематурия, требующая переливания компонентов крови (12%), лихорадка (30%), требующая антибактериальной терапии, повреждение висцеральных органов: печени [25], селезенки [26], желчного пузыря [27], толстой кишки, а также плеврального синуса (8%) [28]. При этом следует отметить, что в настоящее время назначение пери-и послеоперационной антибиотикотерапии, на наш взгляд, является целесообразным для всех пациентов при проведении ЧНЛТ вне зависимости от выраженности лихорадки для профилактики гнойно-воспалительных осложнений.…”
Section: чрескожная нефролитотомияunclassified